CSC577: Software Engineering: theories and principles / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2018)
This course introduces the theories and practices of Software Engineering, which includes software processes, requirement analysis, design, programming practices, verification and validation and software evolution for a large system. It also constructs a solid foundation for understanding and application of principles, techniques, technologies and tools in the development of a good software system. To help students understand these concepts, students will work in a team which lead a project flow through the entire software lifecycle.